Consonants in spontaneous speech of five Danish children with operated cleft palate - an impressionistic analysis - Hutters, Birgit; Brøndsted, Kirsten (Annual Report of the Institute of Phonetics University of Copenhagen, 1986)
This paper examines consonants in spontaneous speech of five 4-5 year old Danish children with persisting speech problems after primary cleft palate surgery. Based on phonetic transcriptions from video-recordings the phonetic and phonological behaviour is described for each child and related to the target norm. The findings are discussed in the light of strategies in cleft palate speech. Furthermore, some aspects of universal and language dependent characteristics in cleft palate speech are treated.